Modulatory Effects of Levodopa on Cerebellar Connectivity in Parkinson's Disease - Mueller, Karsten; Jech, Robert; Ballarini, Tommaso; Holiga, Štefan; Růžička, Filip; Piecha, Fabian A; Möller, Harald E; Vymazal, Josef; Růžička, Evžen; Schroeter, Matthias L (Cerebellum (London, England), 2019)
Levodopa has been the mainstay of symptomatic therapy for Parkinson's disease (PD) for the last five decades. However, it is associated with the development of motor fluctuations and dyskinesia, in particular after several years of treatment. The aim of this study was to shed light on the acute brain functional reorganization in response to a single levodopa dose. Functional magnetic resonance imaging (fMRI) was performed after an overnight withdrawal of dopaminergic treatment and 1 h after a single dose of 250 mg levodopa in a group of 24 PD patients. Eigenvector centrality was calculated in both treatment states using resting-state fMRI. This offers a new data-driven and parameter-free approach, similar to Google's PageRank algorithm, revealing brain connectivity alterations due to the effect of levodopa treatment. In all PD patients, levodopa treatment led to an improvement of clinical symptoms as measured with the Unified Parkinson's Disease Rating Scale motor score (UPDRS-III). This therapeutic effect was accompanied with a major connectivity increase between cerebellar brain regions and subcortical areas of the motor system such as the thalamus, putamen, globus pallidus, and brainstem. The degree of interconnectedness of cerebellar regions correlated with the improvement of clinical symptoms due to the administration of levodopa. We observed significant functional cerebellar connectivity reorganization immediately after a single levodopa dose in PD patients. Enhanced general connectivity (eigenvector centrality) was associated with better motor performance as assessed by UPDRS-III score. This underlines the importance of considering cerebellar networks as therapeutic targets in PD.
Keywords: antiparkinsonika; Levodopa; mapování mozku; Male; levodopa; Nexopathy; magnetická rezonanční tomografie; Functional connectivity; L-dopa; Resting-state magnetic resonance imaging; Brain connectivity; Parkinson’s disease; Adult; Aged; dospělí; mužské pohlaví; senioři; Neural Pathways; Rest; Cerebellum; odpočinek; Brainstem; Brain Mapping; lidé; ženské pohlaví; Humans; Dopaminergic treatment; Cerebellar networks; nervové dráhy; mozeček; Antiparkinson Agents; Eigenvector centrality; Magnetic Resonance Imaging; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Middle Aged